Manganese Dioxide Nanowires of Tunable Dimensions Synthesized via a Facile Hydrothermal Route - Kong, Ying Ying; Pang, Suh Cem; Suk, Fun Chin (Hindawi Publishing Corporation, 2015)
Manganese dioxide (MnO2) nanowires of tunable dimensions were successfully synthesized via the facile water-bathing hydrothermal route. Homogeneous solution mixtures of KMnO4 and MnSO4 of varying compositions were being aged in a thermostated water bath under controlled conditions. The dimensional aspect ratios of MnO2 nanowires formed were readily modulated by varying synthesis parameters such as the initial concentration of chemical precursors, reaction temperature, and aging duration. At fixed initial precursor concentrations, the mean diameter of MnO2 nanowires decreased slightly from 57 nm to 53nm with increased reaction temperature from 60∘C to 90∘C. The mean diameter of MnO2 nanowires decreased linearly within the range of 104 nm and 35nm as the initial concentration of both precursors was increased in turn within the range of 10mmol and 40mmol at fixed aging temperature and duration. Upon aging for 2 to 24 hours at 80∘C, the mean diameter and length of MnO2 nanowires were observed to vary within the range of 33–55 nm and 0.69–2.68